Peran Badan Permusyawaratan Desa (BPD) Sebagai Lembaga Demokrasi Lokal: (Studi di Desa Umaklaran, Kecamatan Tasifeto Timur, Kabupaten Belu) (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This research will explain the role of the Village Consultative Body as a Local Democracy that occurs in Umaklaran Village. Through a Village democratization approach and analyzing the democratic role of the Village Consultative Body (BPD) in the dynamics of governance in the Village with its existence as a Village Democracy institution, in Umaklaran Village, East Tasifeto District, Belu Regency. In this research, to explain the role and analyze the role of the Village Consultative Body in the dynamics of village governance using the theory of Role and Democracy. The method used in this research is a qualitative method with a descriptive approach, and data collection techniques in the form of interviews, observation and documentation studies. In this research it can be illustrated that the role of the BPD as a democratic institution in Umaklaran Village, East Tasifeto sub-district, Belu Regency, is still not working well or is not optimal, this is based on the minimal knowledge and low educational background of the BPD itself, apart from that disharmony in the relationship between the BPD and the village government. So the democratization process in Umaklaran Village has not gone well to date.